THE APPLICABILITY OF INTERNATIONAL HUMANITARIAN LAW IN CASE OF NUCLEAR WAR (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The applicabilityn of international humanitarian law in case of nuclear war.